2016
DOI: 10.1177/0954008315615396
|View full text |Cite
|
Sign up to set email alerts
|

Ion irradiation on polymer electrolyte films

Abstract: Two polymer (poly(ethylene oxide) and poly(vinylpyrrolidone))-based sodium ion conducting systems have been studied. The conductivity and related parameters has been compared after irradiation with that before irradiation. The complex impedance spectroscopic tools have been used to determine the ionic conductivity, dielectric constant, number of charge carriers, and its corresponding mobility of the two systems. Modulation in conductivity of the systems has been correlated and attributed to change in crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This is possibly due to the size of the filler and plasticizer molecule compared to the polymer molecule, which can penetrate easily into the polymer matrix. 27 Figure 3 shows the plot of temperature dependence of maximum conducting plasticized polymer nanocomposite electrolyte, while its Cole–Cole plot is shown in Figure 4. It shows linear dependence of ionic conductivity on temperature or the sample showed Arrhenius behavior.…”
Section: Resultsmentioning
confidence: 99%
“…This is possibly due to the size of the filler and plasticizer molecule compared to the polymer molecule, which can penetrate easily into the polymer matrix. 27 Figure 3 shows the plot of temperature dependence of maximum conducting plasticized polymer nanocomposite electrolyte, while its Cole–Cole plot is shown in Figure 4. It shows linear dependence of ionic conductivity on temperature or the sample showed Arrhenius behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the effect shall be clear. It has already been observed 14 that an ion of higher radii (C 5+ ) results to faster amorphization of the films—due to the formation of relatively larger (local) pockets.…”
Section: Methodsmentioning
confidence: 95%
“…Irradiating of Li 3+ ion at high energy of 60 MeV on two different electrolytes of PEO-NaI and PVP-NaI showed increment in conductivity as compared to unirradiated electrolyte films [77]. Besides conductivity, higher values for number of mobile ions, ionic mobility and dielectric constant have been reported for the solution-cast-prepared SPE after ion-beam irradiation [77]. PAN-based SPE having LiBOB salt also exhibited enhancement in conductivity and transport properties (n, µ and D) after being radiated with a gamma-ray dose of 15 kGy [78].…”
Section: Treatment Of Spesmentioning
confidence: 94%
“…Analyses from DSC and X-ray diffraction (XRD) demonstrated that the former have a lower melting temperature (67.6 • C) and are more amorphous in nature, with reduced crystallinity, than the latter (69.4 • C melting temperature and more crystalline), while FTIR results indicated that the polymer chain was disrupted and degraded after irradiation [76]. Irradiating of Li 3+ ion at high energy of 60 MeV on two different electrolytes of PEO-NaI and PVP-NaI showed increment in conductivity as compared to unirradiated electrolyte films [77]. Besides conductivity, higher values for number of mobile ions, ionic mobility and dielectric constant have been reported for the solution-cast-prepared SPE after ion-beam irradiation [77].…”
Section: Treatment Of Spesmentioning
confidence: 95%